(untitled) (Bangladesh Journal of Medical Science, 2018)
Aim of study: To assess knowledge, attitude and practice of primary care physicians offering primary health care (PHC), toward adult vaccination and their own vaccination coverage as well as to identify reasons for low vaccination coverage. Methodology: A cross-sectional study design, this study included 103 PHC physicians in Abha City. A self-administered questionnaire was designed by the researcher for data collection. Results: About three fourths of PHC physicians (73%) had poor knowledge, while 21% had moderate knowledge and only 6% had good knowledge, while 41% had positive attitude toward adult vaccination, 49% had neutral attitude while 10% had negative attitude. Most PHC physicians (70%) had poor practice regarding adult vaccination, while 20% had moderate practice and 10% had good practice. PHC physicians’ knowledge was significantly better among older and non-Saudi physicians (p<0.001 and p=0.001, respectively). PHC physicians’ positive attitude toward adult vaccination was significantly higher among female participants (p=0.013), among Non-Saudi physicians (p=0.004) and among those with experience in primary health care more than 10 years (p=0.044). PHC physicians’ good practice regarding adult vaccination was significantly higher among older physicians and among those with experience in primary health care more than 10 years (p=0.004). The most frequently stated reasons for low adult vaccination coverage were “Lack of coordinated immunization programs for adults” (63.1%), “Physicians do not inform patients about adult vaccination because they do not have enough time” (61.2%) and “Lack of availability of up-to-date records and recording systems” (55.3%). Conclusions: Knowledge of PHC physicians in Abha City regarding adult vaccination is suboptimal. Most of them do not have negative attitude toward adult vaccination. Their practice regarding adult vaccination is mostly poor. There are several obstacles against implementing vaccination of adults. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.369-381